Symptom burden and lived experiences of patients, caregivers and healthcare professionals on the management of malignant bowel obstruction: A qualitative systematic review. (June 2022) - Baddeley, Elin; Mann, Mala; Bravington, Alison; Johnson, Miriam J; Currow, David; Murtagh, Fliss E M; Boland, Elaine G; Obita, George; Oliver, Alfred; Seddon, Kathy; Nelson, Annmarie; Boland, Jason W; et al.
Background: Malignant bowel obstruction occurs in up to 50% of people with advanced ovarian and 15% of people with gastrointestinal cancers. Evaluation and comparison of interventions to manage symptoms are hampered by inconsistent evaluations of efficacy and lack of agreed core outcomes. The patient perspective is rarely incorporated. Aim: To synthesise the qualitative data regarding patient, caregiver and healthcare professionals' views and experience of malignant bowel obstruction to inform the development of a core outcome set for the evaluation of malignant bowel obstruction. Design: A qualitative systematic review was conducted, with narrative synthesis. The review protocol was registered prospectively (https://www.crd.york.ac.uk/prospero, CRD42020176393). Data sources: MEDLINE, EMBASE, CINAHL, PsycINFO and Scopus databases were searched for studies published between 2010 and 2021. Reference lists were screened for further relevant publications, and citation tracking was performed. Results: Nine papers were included, reporting on seven studies which described the views and experiences of malignant bowel obstruction through the perspectives of 75 patients, 13 caregivers and 62 healthcare professionals. Themes across the papers included symptom burden, diverse experiences of interventions, impact on patient quality of life, implications and trajectory of malignant bowel obstruction, mixed experience of communication and the importance of realistic goals of care. Conclusion: Some of the most devastating sequelae of malignant bowel obstruction, such as pain and psychological distress, are not included routinely in its clinical or research evaluation. These data will contribute to a wider body of work to ensure the patient and caregiver perspective is recognised in the development of a core outcome set.